Quality of life evaluation in patients affected by osteoarthritis secondary to congenital hip dysplasia after total hip replacement - Tellini, Alessandra (Springer Milan, 2008)
BACKGROUND: The aim of the study was to evaluate the quality of life (QoL) in patients affected by osteoarthritis (OA) secondary to congenital hip dysplasia (CHD) and treated by hip arthroplasty. METHODS: We prospectively treated 40 patients admitted to our hospital between 2001 and 2006. Each patient was asked to answer to two questionnaires: WOMAC and MOS SF-36. Patients were evaluated four months before surgery and once they had achieved postoperative rehabilitation. Pre- and postoperative results were analyzed and compared with the international literature on patients affected by OA and also with a healthy population. RESULTS: Pre- and post-operative results: WOMAC: pain 14.06–0.84; stiffness 4.26–0.52; function 42.68–5.39. SF-36: physical function 18.55–84.52; role physical 28.33–87.10; body pain 23.26–83.39; general health 55.19–81.74; vitality 32.74–72.10; social function 43.55–84.66; role emotional 68.82–93.55; mental health 48.77–79.35. All results were statistically significant. CONCLUSIONS: The study reports an important QoL improvement in patients affected by arthritis secondary to CHD that underwent hip surgery, and underlines differences with respect to primary OA. QoL evaluation cannot replace either clinical and instrumental evaluation or the physician’s experience, but it can give weight to the patient’s expectations, and may be considered an efficient test for medical and surgical treatments.